FINTECH AND FINANCIAL INCLUSION FINTECH AND FINANCIAL INCLUSION: OPPORTUNITIES AND CHALLENGES IN THE DIGITAL ECONOMY - Febriana, Widia; Komala, Rina; Anggriani, Rini; Rizki, Olivia Sonata (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The rapid growth of financial technology (fintech) has significantly reshaped the landscape of the global digital economy, particularly in expanding access to financial services. Fintech innovations such as mobile banking, peer to-peer lending, and digital payment systems have created new opportunities for individuals and small businesses that were previously excluded from the formal financial sector. By lowering transaction costs, increasing efficiency, and offering user-friendly platforms, fintech has the potential to drive financial inclusion and stimulate broader economic participation. However, alongside these opportunities, several challenges persist. Regulatory gaps, cybersecurity threats, and unequal access to digital infrastructure pose risks that may limit the benefits of fintech adoption. In developing economies, digital literacy and trust in online financial systems remain key barriers to inclusive growth. Moreover, the rapid pace of innovation often outpaces existing policy frameworks, raising concerns over consumer protection and financial stability. This paper examines the dual role of fintech in advancing financial inclusion while highlighting the challenges that must be addressed to ensure equitable and sustainable growth. Drawing from global trends and case studies, it emphasizes the need for collaborative strategies involving governments, private sectors, and international institutions. The findings suggest that a balanced approach combining innovation, regulation, and education is essential to maximize the opportunities of fintech while mitigating its risks. Ultimately, fintech has the potential to serve as a transformative tool in the digital economy if inclusivity and resilience are placed at the center of its development.